Izobraževanje - možni dejavnik krepitve moči in vpliva starejših odraslih - Kump, Sonja (Družboslovne razprave, 2005)
Education of older adults (in the so-called the third age) is getting more and more significant among different activities intended for elderly above all because it enhances the power of older people and at the same time people reduces their social exclusiveness. The aim of this paper is to examine closely the actual state of affairs and the possibilities of older adults' education. The article deals with a secondary analysis of data that were collected in two Slovene researches on participation of adults in education inthe year 1987 and 1998. The purpose of the analysis is to examine the changes in the participation of older adults, their motivation for education and barriers that have dissuaded elders from education. Special attention in the paper is devoted to the thesis that only education based on the principles of critical educational gerontology could reduce marginality of older adults and enhance their power. The authors state that an offer of education for older people has improved between 1987 and 1998, while the participation of older adults has declined. In the last study, however, older adults stated that impediments, such as, poor offer of programmes, were reasons for their diminished participation in education.
Keywords: stari ljudje; education; izobraževanje; izobraževanje odraslih; družbena vloga